2021
DOI: 10.3390/ma14143914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcination Temperature and Chemical Composition of PAN-Derived Carbon Microfibers on N2, CO2, and CH4 Adsorption

Abstract: This work investigates the interplay of carbonization temperature and the chemical composition of carbon microfibers (CMFs), and their impact on the equilibration time and adsorption of three molecules (N2, CO2, and CH4). PAN derived CMFs were synthesized by electrospinning and calcined at three distinct temperatures (600, 700 and 800 °C), which led to samples with different textural and chemical properties assessed by FTIR, TGA/DTA, XRD, Raman, TEM, XPS, and N2 adsorption. We examine why samples calcined at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…In the formula, C oil represents the concentration of oil in the water sample, mg L −1 ; Q represents the concentration of oil in the n-hexane extract obtained from the standard curve, mg L −1 ; V 1 represents the volume of n-hexane extraction solvent, mL; and V 2 represents the volume of the sample, mL. The control of the preparation formula (biochar dosage, Na 2 SiO 3 dosage and NaHCO 3 dosage) could change the surface structure of biochar to a certain extent and affect its adsorption performance for NH 4 + -N [15]. Therefore, in this study, the orthogonal experiment method was used to investigate the effect of the BCCP preparation formula on NH 4 + -N adsorption (Table 3).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…In the formula, C oil represents the concentration of oil in the water sample, mg L −1 ; Q represents the concentration of oil in the n-hexane extract obtained from the standard curve, mg L −1 ; V 1 represents the volume of n-hexane extraction solvent, mL; and V 2 represents the volume of the sample, mL. The control of the preparation formula (biochar dosage, Na 2 SiO 3 dosage and NaHCO 3 dosage) could change the surface structure of biochar to a certain extent and affect its adsorption performance for NH 4 + -N [15]. Therefore, in this study, the orthogonal experiment method was used to investigate the effect of the BCCP preparation formula on NH 4 + -N adsorption (Table 3).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The same phenomenon existed in the research of Chen et al (2018) who found that the surface area and pore volume of bentonite increased to 56.09 and 0.0611 cm 3 g −1 when the calcined temperature was 400 • C, respectively, but sharply declined to 30.53 and 0.051 cm 3 g −1 at 800 • C. Yan et al (2018) prepared a kind of porous diatomite microsphere by spray drying method and the methylene blue adsorption capacity and removal efficiency demonstrated the maximum values when the calcined temperature was 600 • C, and decreased when the temperature rose. Ojeda-López et al (2021) found that adsorbent/adsorbate interactions for CO 2 , CH 4 , and N 2 were inversely proportional to calcined temperature (CMF-600 > CMF-700 > CMF-800) by the mean of the isosteric enthalpy of adsorption measurements.…”
Section: Effect Of Calcined Program On Ammonia Nitrogen Adsorption By...mentioning
confidence: 98%
“…(ii) Trapped nitrogen could not be released because of its affinity for the heterogeneous surface of ACFs. (iii) The nearsolid state condensation of the adsorbate occurred at the entryway of pores [36,37]. The specific surface area of ACFs was calculated using the Brunauer-Emmett-Teller (BET) method utilizing the adsorption data in the P/P0 range of 0.05 to 0.30.…”
Section: Surface Area and Porosity Analysesmentioning
confidence: 99%